Manajemen Supervisi Pendidikan Islam - Abdussofi, Khaedar; Sunhaji, Sunhaji (Indo-MathEdu Intellectuals Journal, 2026)
Islamic educational supervision is a crucial instrument for improving the quality of learning in Islamic institutions, emphasizing the integration of spiritual, moral, and academic aspects. This study analyzes the concept, implementation, and effectiveness of supervision in developing teacher competence and learning management quality using a qualitative, literature-based approach. The review includes the works of Mulyasa, Al-Nahlawi, and al-Abrasy, as well as empirical studies by Zepeda, Glickman, Kim, and Cho. The findings indicate that Islamic educational supervision has unique dimensions such as spiritual development, moral exemplarity, and the reinforcement of tarbiyah values, which are less prominent in conventional models. Systematic academic supervision enhances lesson planning, pedagogical skills, and teacher professionalism. The study proposes a holistic supervision model that integrates Sharia principles, humanistic approaches, and modern techniques, strengthening Islamic institutions through reflective evaluation, consultation, and spiritual guidance, positioning supervision as a process of empowering teachers toward professionalism and moral integrity.